2016
DOI: 10.1155/2016/2349514
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vinasse Application in the Structure and Composition of the Bacterial Community of the Soil under Sugarcane Cultivation

Abstract: Although the use of vinasse as a waste helps replenish soil nutrients and improves the quality of the sugarcane crop, it is known that vinasse residues alter the diversity of bacteria naturally present in the soil. The actual impacts of vinasse application on the selection of bacterial taxa are not understood because no studies have addressed this phenomenon directly. Analysis of 16S rRNA gene clone sequences from four soil types showed that the soil planted with sugarcane and fertilized with vinasse has a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
2
11
0
2
Order By: Relevance
“…Although organic fertilizers are used to increase sugarcane productivity through nutrient availability to plants, they can also affect soil microbial community and physicochemical soil factors [7,14,20,52], and key biogeochemical processes associated with GHG emissions, such as decomposition, respiration, nitrification and denitrification [23,25,53]. Moreover, the use of organic residues has resulted in the increase of C and N labile organic forms [47][48][49], which has been used as soil quality indicator due to rapid alteration according to soil practice management [54].…”
Section: Use Of Organic Fertilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although organic fertilizers are used to increase sugarcane productivity through nutrient availability to plants, they can also affect soil microbial community and physicochemical soil factors [7,14,20,52], and key biogeochemical processes associated with GHG emissions, such as decomposition, respiration, nitrification and denitrification [23,25,53]. Moreover, the use of organic residues has resulted in the increase of C and N labile organic forms [47][48][49], which has been used as soil quality indicator due to rapid alteration according to soil practice management [54].…”
Section: Use Of Organic Fertilizersmentioning
confidence: 99%
“…Omori et al [52] reported increases in bacterial diversity after vinasse application to the soil and revealed that this by-product of the sugar-ethanol industry promotes the participation of soil microbial community members in N and Fe cycling. The authors showed that Acidobacteria Gp3 and Gp4 were most abundant in the vinasse-amended soil.…”
Section: Use Of Organic Fertilizersmentioning
confidence: 99%
“…Kielak et al (2016) recently reviewed the genomic and physiological characteristics of Acidobacteria and showed that there are still many gaps to understanding the functional role of this bacterial phylum in the soil C degradation process. Despite of this lack of biological and ecological information for Acidobacteria, previous studies in agricultural soils have shown that both microbial C degradation processes and acidobacterial community can be affected by soil management (Craine et al, 2007; Navarrete et al, 2015a; Omori et al, 2016; Wang et al, 2018; Lian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of organic byproducts and wastes applied to agricultural soils have already been extensively assessed, with results showing that their beneficial effects on soil properties that far outweighed the negative impacts [2]. It has been proven that soil treatments with stillage enhance microbial biodiversity and are particularly beneficial for the species involved in the N cycle [11]. Improvements in the microbial activity are crucial for the transformations of organic matter and nutrients in the soils, making them available to crops.…”
Section: Introductionmentioning
confidence: 99%
“…Soil treatments with stillage allow for the recycling of nutrients, which on the one hand contributes to the protection of natural resources, and on the other minimizes the costs associated with the use of mineral fertilizers on a local scale [2,3,7,11]. This is particularly important in the case of cultivation of maize, which is the crop with high nutritional requirements and a negative impact on soil organic matter contents [15,16].…”
Section: Introductionmentioning
confidence: 99%